Gender and Identity in Post-Colonial English Novels: A Comparative Study (London Journal of Research In Humanities and Social Sciences, 2024)
This study examines the intricate interplay of gender and identity within the framework of post-colonial English novels, exploring how these narratives reconstruct and challenge colonial power structures. By analyzing selected texts from diverse post-colonial contexts, the paper reveals the multifaceted ways in which gender roles and personal identities are renegotiated in the aftermath of colonial rule. The analysis emphasizes the intersectionality of race, class, and culture, shedding light on how these factors shape the protagonists' identities and their resistance to patriarchal and imperialist norms. Employing a comparative approach, the study draws parallels between novels from Africa, South Asia, and the Caribbean, showcasing the universal yet context-specific struggles of post-colonial identities. The findings contribute to a deeper understanding of the socio-political undercurrents of post-colonial literature and its enduring relevance in contemporary debates on identity politics and gender equity.
Keywords: teaching; learning; language; diversity; proficiency